METABOLIC SYNDROME IN PREGNAT FEMALES PRESENTING IN A TERTIARY CARE HOSPITAL AND ITS IMPACT ON INCIDENCE OF PRE -TERM DELIVERY. - Imran, Ayesha; Yaqub, Umairah; Aslam, Wafa; Yazdani, Tehreem; Khawar, Zarmeen; Ahmed, Naveed (Pakistan Armed Forces Medical Journal, 2021)
Objective: To find the association of preterm delivery with metabolic syndrome in females presenting in a tertiary care hospital.Study Design: Cohort study.Place and Duration of Study: Department of Obstetrics & Gynecology, Combined Military Hospital Kharian, from May 2020 to Oct 2020.Methodology: A total of 150 females fulfilling inclusion criteria were enrolled in the study which were divided into two equal groups ‘A’ and ‘B’. Group ‘A’ was with metabolic syndrome and group ‘B’ without it. These females were followed in OPD till active labor, assessed and followed till delivery of fetus. If delivery occurred before 37 weeks, then preterm delivery was labeled. All this information was recorded on a pre-designed proforma.Results: The risk for preterm delivery was 2.18 times higher in group ‘A’ as compared to group ‘B’. (Relative Risk = 2.18, CI (95%) 1.1529 - 4.12).Conclusion: There is a strong association of preterm delivery with metabolic syndrome in females.